2019
DOI: 10.21203/rs.2.15549/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surgical site infection prevalence and associated factors in Hawassa University comprehensive specialized hospital, southern Ethiopia.

Abstract: Background Surgical site infections (SSIs) continue the main problem in health care facilities, causing the prolonged length of stay, considerable morbidity, mortality, and the extra cost to patients after surgery. The aim of this study was to determine the prevalence of SSIs and explore its associated factors among surgical patients at Hawassa university comprehensive specialized hospital, southern Ethiopia.Methods A hospital-based cross-sectional study design was conducted among post-operative patients on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
4
4
1
Order By: Relevance
“…This study found that the prevalence of SSI was higher in patients with dirty and contaminated wound types than those patients with clean wounds. This finding is consistent with reports from Uganda, 15 Hawassa, Ethiopia, 16 and Mekelle, Ethiopia. 11 The significant influence of endogenous contamination during the operation or exogenous contamination during the wound care procedure might be a scientifically justifiable reason.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study found that the prevalence of SSI was higher in patients with dirty and contaminated wound types than those patients with clean wounds. This finding is consistent with reports from Uganda, 15 Hawassa, Ethiopia, 16 and Mekelle, Ethiopia. 11 The significant influence of endogenous contamination during the operation or exogenous contamination during the wound care procedure might be a scientifically justifiable reason.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the overall prevalence of SSI was 11.8% which is consistent with the study carried out in Rwanda (10.2%) 14 and Bahir Dar, Ethiopia (10.2%), 7 but relatively lower when compared with studies conducted in Uganda (16.4%), 15 Egypt (67.6%), 8 Hawassa, Ethiopia (24.6%), 16 and Mekelle, Ethiopia (29.8%). 11 Besides, this finding is higher compared with studies conducted in Peru (2.5%) 17 and Saudi Arabia (2.2%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations